(untitled) (Comprehensive Journal of Science, 2025)
This study aims to evaluate the impact of physical and chemical factors specifically pH and temperature—on the stability and degradation of two fluoroquinolone antibiotics: Ofloxacin and Ciprofloxacin in aqueous solutions. Standard solutions of varying concentrations were prepared, and their absorbance and maximum wavelength (λ max) were measured using a UV-Vis spectrophotometer under different pH and temperature conditions.The results showed that an acidic medium (pH = 4) increased the absorbance of both antibiotics, with slight changes in λ max. Elevated temperatures led to a decrease in absorbance, indicating gradual thermal degradation of the compounds.The study highlights the importance of understanding environmental influences on antibiotic efficacy and recommends further research involving additional factors and longer exposure periods to enhance pharmaceutical stability assessments.